2021
DOI: 10.18608/jla.2021.7227
|View full text |Cite
|
Sign up to set email alerts
|

What Do You Mean by Collaboration Analytics? A Conceptual Model

Abstract: Using data to generate a deeper understanding of collaborative learning is not new, but automatically analyzing log data has enabled new means of identifying key indicators of effective collaboration and teamwork that can be used to predict outcomes and personalize feedback. Collaboration analytics is emerging as a new term to refer to computational methods for identifying salient aspects of collaboration from multiple group data sources for learners, educators, or other stakeholders to gain and act upon insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 167 publications
1
18
0
Order By: Relevance
“…Specifically, the paper—through the conceptualisation of the four phases of peer‐review process—demonstrated how a theoretical model can be used to structure the program of research, development, deployment, and evaluation by addressing a problem (ie, trust in a peer‐review system) that may emerge in practice. This is an important contribution that complements existing calls for integration of theory and design with computational methods of AI and data science in learning analytics (Gašević et al, 2017; Martinez‐Maldonado et al, 2021). Second, the studies reported in the paper provide fresh empirical insights that can inform the development of future AI‐driven learning analytic systems that seek to enhance trustworthiness of peer‐review.…”
Section: Discussionmentioning
confidence: 69%
“…Specifically, the paper—through the conceptualisation of the four phases of peer‐review process—demonstrated how a theoretical model can be used to structure the program of research, development, deployment, and evaluation by addressing a problem (ie, trust in a peer‐review system) that may emerge in practice. This is an important contribution that complements existing calls for integration of theory and design with computational methods of AI and data science in learning analytics (Gašević et al, 2017; Martinez‐Maldonado et al, 2021). Second, the studies reported in the paper provide fresh empirical insights that can inform the development of future AI‐driven learning analytic systems that seek to enhance trustworthiness of peer‐review.…”
Section: Discussionmentioning
confidence: 69%
“…To our knowledge, there have been no attempts to empirically map out the entire space between data, meric, outcome, and constructs, which is difficult to achieve not only due to the sheer range in metrics and outcomes used, but also due to the diverse ways that metrics and outcomes are connected [11,16]. Our empirical survey of theory use in MMCA research is an additional novel contribution that responds to the call for more theory integration in social analytics [9,17].…”
Section: Introductionmentioning
confidence: 97%
“…Our work differentiates itself from prior reviews by scope, looking at MMCA papers in both education and social computing. While there is work in both fields that shares the same goal of detecting and supporting collaboration [9], there is little communication between the two fields, and reviews either focus on multimodal learning analytics (MMLA; e.g., [4,10]), or social computing research on collaboration (e.g., [11,12]). Additionally, prior reviews in MMLA or social computing presented models of research (e.g., [13,14]) or surveyed the types of collaborative outcomes that research focused on [10,11], or organized the types of data sources used [9,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…-Caveat: recent research on learning analytics does in fact make links between "e-data" (e.g., from group artefacts, speech and groupware logs) and specific higher-order constructs such as symmetry of action and transactivity in collaboration (e.g., Martinez-Maldonado et al, 2021); but these constructs, as well as initial data analysis, need to be situated within and guided by more general theories of dialogue, cognition and collective activity.…”
mentioning
confidence: 99%